Educador social: formação e prática - Jantke, Regina Vazquez Del Rio (2012)
From the interest for the work done by the social educator, a research was done by a literature that in which measured the formation and practice of this professional, contributes for the personal and social transformations of the students. Via a theoretical study, it was intended to verify how presently are the formation and practice of the social educator by the analysis of the Social Pedagogy historical panorama, by the social educator s profile and some of the own abilities and competencies of that professional function. It was found that the practice needs systematization, deepness and approach with the pedagogical theories, aiming to substantiate the social educators work, to the creation of new socio educative methodologies. To back up this reflection, searched for knowing the recent scientific production, especially from Brazilian and Spanish researchers, in terms of the expectations and obstacles in the educators formation in the contemporaneity. Consider necessary a theoretical formation that meets the social educator s demands that are part of a new context of knowledge, counting for this, that by university formation programs, there is an effective partnership between the Higher Education Institutions and public and private entities, in the preparation of this curriculum. By the formation supported by a comprehensive and critical knowledge s basis, in terms of inclusive the public politics, to a social rights and duties vision and political engagement, the social educator will contribute with his professional actuation together with the community where he acts, in the awakening of the comprehension of his reality, searching for a possible change in his socioeconomic condition